New Public Management in The Changing Status of Higher Education Institution in Indonesia - Muhammad Muhammad (Jawda: Journal of Islamic Education Management, 2021)
Global competition among universities in the world has become more challenging over years. This makes it demanding not only for universities in Indonesia to create positive improvements but also for the government to adapt with its innovations and policy initiatives. Meanwhile, New Public Management approach which was initially introduced in 1990s has been proposing administrative reforms on the old inefficient bureaucracy. In response to this, universities along with the government have been incorporating some aspects of The New Public Management theory in order for them to strive in global competition. This study seeks to analyze the changing status of Indonesian universities. It further discusses how some aspects of New Public Management are incorporated in university’s administration. This Indonesian case study argues that NPM values has influenced the changing system of universities in Indonesia. NPS still exists partially if not fully, in Indonesian universities despite the problem of public acceptance responding to the government’s policy on university reforms.